Anomalous fracture behavior in borosilicate glass facilitated by stress-induced molecular rearrangements - Jet Lem; Eric R. Sung; Alexei A. Maznev; Yun Kai; Alan F. Schwartzman; Steven E. Kooi; Keith A. Nelson (Proceedings of the National Academy of Sciences, 2025)
Silica-based glasses have found numerous applications in every field of human endeavor. Understanding their mechanical behavior under high strain rates is essential for the use of these materials in extreme environments. We report on a highly unusual fracture behavior observed in borosilicate glass facilitated by stress-induced molecular rearrangements, allowing the glass to withstand tensile stresses up to 11 GPa. Converging surface acoustic waves (SAW) with controlled amplitude are generated optically and used to investigate the high-strain-rate (10 8 s −1 ) fracture behavior of borosilicate glass. Above a tensile stress threshold of 6 GPa, fracture of the glass surface is observed, characterized by ejection of material and radial cracking. Unexpectedly, upon further increase of the SAW stress, a second threshold of 8 GPa tensile stress is observed above which the fracture probability dramatically decreases. Raman spectra and nanoindentation measurements of shocked samples indicate significant changes in the topology and coordination numbers of silicon and boron atoms in the amorphous network. These results suggest the ability of thresholded atomic rearrangements to serve as an intrinsic high-strain-rate toughening mechanism for enhanced fracture toughness in amorphous borosilicate glass under dynamic strain conditions.